10. STATUS AND SOME FACTORS RELATED TO TOOTH CAVITY DISEASE IN PRIMARY SCHOOL PUPILS OF MONG PEOPLE IN MU CANG CHAI DISTRICT YEN BAI PROVINCE 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: Determine the status and some factors related to dental caries in Mong primary school Pupils in Mu Cang Chai district, Yen Bai province 2023.Research method: Cross-sectional descriptive study with analysis was conducted through direct interviews and dental examinations for 700 pupils to determine the status of tooth decay and some factors related to tooth decay.Results: The rate of Pupil with tooth decay accounted for 65.1%. Rate of decayed baby teeth account for 64,9%, decayed permanent teeth is 35,1%. Pupil with decayed 2 teeth account for 22,9%, decayed 3 teeth is 17,6%. The rate of pupils with >3 tooth decayed accounts for 9%. The index of decayed baby teeth in pupils is 3,3, missing teeth is 0,7, filled teeth is 0,1, dmf index is 4,1. The index of decayed permanent teeth is 0,8, missing teeth 0,1, filled teeth 0,1, DMF index 1,03. In baby teeth, the rate of enamel caries accounts for 42,2%, dentin caries accounts for 44,9%, pulpitis accounts for 12,8%. In permanent teeth, enamel caries accounts for 59,4%, dentin caries accounts for 32,5%, pulpitis accounts for 8,1%. Tooth decay is related to Pupils’ knowledge and practice of prevention with p
Keywords: Tooth decay, Oral dental hygiene, Tooth decay index, Mu Cang Chai District.